Splenic injury as a complication of colonoscopy: more common than we think?. (9th September 2015) - Ng, Peter
Abstract : Splenic injury during colonoscopy is thought to be rare. The case reported here would not have been diagnosed if the patient had not presented with a pleural effusion. It is likely that this complication may present with differing severities of clinical features with a significant proportion being thought to be due to expected postcolonoscopy insufflation discomfort. This complication is under-recognised and under-reported and therefore is unlikely to be thought of as a diagnosis. A 63-year-old woman had an elective day case colonoscopy but did not seek medical attention for the abdominal pain following the procedure. She presented to hospital 6 weeks after the procedure with dyspnoea and hypoxia. She was diagnosed with a parapneumonic pleural effusion but the CT scan also discovered a splenic haematoma for which there was no other cause in her history other than the colonoscopy 6 weeks prior.